Reduction of nitric oxide release from alveolar macrophages by a lipocortin peptide - A. M. Kamal; T. D. Tetley; I. R. Witherden; S. F. Smith (Mediators of Inflammation)
Nitric oxide (NO), produced by alveolar macrophages (AM) is used as a marker of respiratory tract inflammation. Lipocortin 1 (Lc-1) is an anti-inflammatory, glucocorticoid-inducible protein. The current aims were to determine whether (a) an Lc-1-derived peptide, Ac2-26, inhibited lipopolysaccharide (LPS)induced NO release by primary AM in vitro and (b) the inhibitory action of dexamethasone was Lc-1-dependent. LPS treatment stimulated NO release from rat AM. Ac2-26 had little effect on unstimulated release, but suppressed LPS-stimulated release at concentrations of 320 nM (320 nM, 10 ± 3%; 3.2 μ M, 15 ± 3%; 32 μ M, 27 ± 4% NO inhibited, mean ± SEM, n=6). Inhibition by dexamethasone of NO release was unaffected by neutralizing anti-Lc-1 indicating that this action is Lc1-independent in primary AM. Nevertheless inhibition of NO release by Ac2-26 (80 μ M) was similar to that of 1 μ M dexamethasone (Ac2-26, 40 ± 6%; dexamethasone, 48 ± 6% NO inhibited, mean ± SEM, n=6).